Multi-objective Optimization and Strength Simulation Analysis of Planetary Reducer with Small Tooth Number Difference - Xia Jianfang; Zhou Shuaihua; Chen Siyu (Jixie chuandong)
Due to the elastic meshing effect existed in planetary reducer with small tooth number difference,its real carrying capacity is many times greater than the calculation value obtained by the traditional gear design theory. Therefore,based on the elastic multi- tooth contact effect,taking the basic parameters of gear as design variables,and a multi- objective optimization model of small tooth difference planetary drive is established,while targeting on maximum efficiency as well as smallest volume and the internal and external gear equal strength of the core unit of the planet wheel. The optimization results show that the internal and external gear strength is close enough,and the meshing efficiency raised to 99. 65%,construction volume decreased by29. 3%. The ANSYS Workbench is applied for the statics simulation of the planetary reducer with small tooth difference. The correctness of the multi- tooth elastic contact load distribution calculation method is verified.The maximum stress position and value is consistent with the theoretical calculation results with the error less than 6. 0%,meeting the engineering accuracy requirements. The validity of the multi- tooth elastic meshing gear design theory and reasonableness of optimization scheme are verified.